Marriages, families and relationships making choices in a diverse society - Lamanna, Mary Ann; Riedmann, Agnes Czerwinski; Stewart, Susan (Cengage Learning, 2018)
"This best-selling text on marriages, families, and relationships combines an authoritative, yet applied approach with a theme that is especially relevant today: making choices in a diverse society. A balance of various theoretical perspectives along with many examples helps you understand how people are influenced by the society around them, how social conditions change in ways that affect family life, the interplay between families and the larger society, and the family-related choices that individuals make throughout adulthood. You'll gain insightful perspectives on the diversity of our modern society, including different ethnic traditions and family forms, and be encouraged to question assumptions and reconcile conflicting ideas and values as you make informed choices in your own life"--Provided by publisher.